Design And Development Of Programming Learning Platform Based On Heuristic Approach In Live Code Module With Iterative And Incremental Method(case Study: Information System Telkom University) - Ekky Novriza Alam; Soni Fajar Surya Gumilang; Muhammad Azani Hasibuan (eProceedings of Engineering, 2015)
Abstract  —Students   of  computer science  in  the  world  have  the  same  problem of  learning   basic programming. Many of students  difficulties in solving the different  problems with the same algorithm solution. Students  may easier to understand the syntax and intent of the statement coding programming language,  however to apply them in the correct  program code is difficult. The effectiveness method  of learning introductory programming is live code method. In this research discussed on the development of live code method in programming learning  platform based on heuristic  approach that called CIDEC Platform as a solution to help student learn programming easier. This platform can help lecturer to make a live code question with own perspective and student can answer question with live code feature without install  anything.  For  platform development,  it used  iterative  and  incremental method  made  in four iteration by involving business  modelling,  requirement analysis,  analysis  and  design, implementation, and testing. Platform based web application is built with by using concept Model-View-Template (MVT) which utilize Python programming language within Django Framework and MySQL database. The live code compiler built with by using Java Development Kit and Ace Editor.  The result  of research is Live Code Module in Programming Learning Platform. For further research, focus development  can develop by upgrade the case sensitive,  add a type of question livecode can compile  or shown to student  and free live code area. So, lecturer can make a  diverse questions of livecode,such as compare  method,check the logic and check a return type. Student  can do coding without specific course.